The multiple benefits of crop diversity - Vernooy, Ronnie; ISSD Africa (2022)
One of the effective strategies for smallholder farmers to adapt to climate change is to diversify their production, e.g., through adding better adapted crops and/or crop varieties to their current basket of crop and variety choices. In this video, produced under the umbrella of the Integrated Seed Sector Africa Theme 3 on Agrobiodiversity, Seeds and Climate Change, farmers from Zimbabwe and researchers from Ghana, Kenya and Zambia, explain the multiple benefits of crop diversity. Script: Ronnie Vernooy, the Alliance of Bioversity International and CIAT.